The lost princess [videorecording (DVD)] - Hajji, Hicham; Camus, Jean-Daniel; McConnell, Jonathan; Roberts, Eric, 1956-; O'Sullivan, Cillian; Dourdan, Gary; Azzabi, Soraya (Gravitas Ventures, 2025)
Billionaire Alec Touati discovers his true destiny when he stumbles upon a haunted castle with a tragic love story. With Nassim and Hana's help, he fights to protect the castle's legacy and fulfill his ancestral purpose.